Multiscale analysis of wave propagation in composite materials - Cattani, C. (Mathematical Modelling and Analysis, 2003)
The multiscale solution of the Klein‐Gordon equations in the linear theory of (two‐phase) materials with microstructure is defined by using a family of wavelets based on the harmonic wavelets. The connection coefficients are explicitly computed and characterized by a set of differential equations. Thus the propagation is considered as a superposition of wavelets at different scale of approximation, depending both on the physical parameters and on the connection coefficients of each scale. The coarse level concerns with the basic harmonic trend while the small details, arising at more refined levels, describe small oscillations around the harmonic zero‐scale approximation.Daugiasluoksnė bangos plitimo kompozicinėse medžiagose analizėSantrauka. Darbe nagrinėjamas Kleino‐Gordono lygčių tiesinėje fazių mikrostruktūrinių medžiagų teorijoje daugiasluoksnio uždavinio sprendimas. Sprendiniui nustatyti naudojamasi bangelių šeima, turinčia harmoninių bangelių prigimti. Jungties koeficientai tiksliai randami ir nusakomi diferencialiniu lygčių rinkiniu. Bangos plitimas yra nagrinėjamas kaip bangelių skirtinguose sluoksniuose aproksimacijos superpozicija, priklausanti tiek nuo fizikinių parametrų, tiek nuo jungties koeficientų kiekviename sluoksnyje. Grubus priartėjimo lygmuo nagrinėja tik harmonines slinktis, kai, tuo tarpu, smulkios detalės, atsirandančios subtilesniuose lygmenyse, aprašo smulkias osciliacijas aplink harmoninę nulinio lygio aproksimaciją.First Published Online: 14 Oct 2010